EFFECTS OF HUMIC ACID, WHEY AND ARBUSCULAR MYCORRHIZAL FUNGI (AM F) APPLICATIONS ON SEEDLING GROWTH AND FUSARIUM WILT IN ZUCCHINI (C ucurbita pepo L.) - S. Sensoy; E. Ocak; S. Demir; S. Tufenkci (Journal of Animal and Plant Sciences, 2013)
The effects of Arbuscular Mycorrhizal Fungi (AMF, Gigaspora margarita), whey (50 ml kg-1), and Humic acid (HA, 500 mg kg-1) applications on seedling growth and Fusarium wilt (FON, Fusarium oxysporum sp. niveum) in hybrid zucchini (Cucurbita pepo L.) cultivar Focus F1 were investigated. The study was consisted of total 16 treatments including different combinations of FON, AMF, humic acid and whey. There were significant effects of the treatments on seedling growth and some nutrient contents. The treatment which had the highest suppression on Fusarium wilt was the single AMF treatment followed by triple application of AMF, HA, and whey.
Keywords: AMF; fusarium wilt; humic acid; whey; zucchini